Pengaruh Pelaksanaan Prinsip-prinsip Good Governance terhadap Kinerja Organisasi (DISDUKCAPIL Kabupaten Magetan) - Wahyu Millensyah, Erwing; Supriyono, Bambang; Eko Wismanu, Rendra (Jurnal Ilmiah Administrasi Publik, 2023)
The Background of this research is by the existence of Undang-Undang Number 23 of 2014 concerning local Government. The purpose of this study is to determine the relationship and influence between the implementation of the principles of good governance on organizational performance at Dinas Kependudukan dan Pencatatan Sipil Kabupaten Magetan. This research is quantitative research. The variables in this study are the principles of Good Governance (X) and Organizational Performance (Y). The results of the product moment correlation analysis show that the implementation of the Good Governance Principles has a positive and significant relationship to Organizational Performance (Y) and the results of a simple linear regression analysis show that the implementation of the Good Governance Principles has a positive and significant impact on Organizational Performance (Y). Based on this research, suggestions that can be submitted are opening scheduled electronic-based discussion forums so that people's aspirations can be conveyed also open tenders and choose vendors with the lowest price offers but still pay attention to the quality of goods/ services.